Recent Advances in Catalytic Transformations Involving Copper Acetylides - Adeleke, A. Francis; Brown, Alexander P. N.; Cheng, Li-Jie; Mosleh, Kari A. M.; Cordier, Christopher J. (Synthesis, 2017)
This review will discuss recent advances in catalytic transformations involving copper acetylides. The content is organized according to the site of functionalization: cross-couplings and direct nucleophilicity (C1-functionalization), formal cycloadditions (C2-functionalization), and propargylic substitutions (C3-functionalization).1 Introduction2 Cross-Couplings3 Direct Nucleophilicity4 Formal Cycloadditions5 Propargylic Substitutions6 Conclusions and Perspectives
Keywords: copper; catalysis; alkynes; enantioselectivity; alkyne complexes; asymmetric catalysis